2021
DOI: 10.1039/d1gc02529e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical strategies for N-cyanation of secondary amines and α C-cyanation of tertiary amines under transition metal-free conditions

Abstract: Electrochemical N-cyanation of secondary amines and α C-cyanation of tertiary amines have been established under transition metal-free conditions, which provide cyanamides and nitriles with good functional group tolerance from simple systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Electrochemical oxidation using halogen mediators is also useful for forming C−N bonds [29–45] . In 2018, Zeng reported the electrochemical synthesis of lactams via the intramolecular amination of amides using NaBr (Scheme 6).…”
Section: Electrochemical Reactions Using Halogen Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical oxidation using halogen mediators is also useful for forming C−N bonds [29–45] . In 2018, Zeng reported the electrochemical synthesis of lactams via the intramolecular amination of amides using NaBr (Scheme 6).…”
Section: Electrochemical Reactions Using Halogen Mediatorsmentioning
confidence: 99%
“…In 2021, Fu and Cai reported electrochemical N ‐cyanation using Bu 4 NBr as a halogen mediator (Scheme 7). [30] In the presence of Bu 4 NBr and KF, the electrolysis of secondary amines with trimethylsilyl cyanide (TMSCN) gave cyano‐substituted compounds. The desired products were not obtained in the absence of Bu 4 NBr; thus, Bu 4 NBr is essential for the reaction.…”
Section: Electrochemical Reactions Using Halogen Mediatorsmentioning
confidence: 99%
“…[ 109 ] Cai and colleagues invented N‐cyanation of secondary amines and the cyanation of tertiary amines without transition metals. [ 110 ] As a solvent, acetonitrile is used to prepare the corresponding cyanated products using the cyano source trimethylsilyl cyanide, additives KF, and tetrabutylammonium bromide. A study of the N‐cyanation process showed that tetrabutylammonium bromide played an important role, indicating that free radicals played a role in the process.…”
Section: Advanced Electrocatalysis For Anodic Reactionsmentioning
confidence: 99%
“…These discoveries offer the possibility of producing formic acid at low temperatures using earth-abundant electrocatalysts from glycerol. Au PNR aerogels with varying percentages of [110] faces (from 12 to 36%) were prepared and used as the catalyst in the ethylene glycol oxidation reaction. [64] The specific activity and long-term stability are significantly influenced by the percentage of the [100] and [111] components added together as well as the fraction of the [110] factors.…”
Section: Polyhydric Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation